Monolayer MoSe2 Grown by Chemical Vapor Deposition for Fast Photodetection - Chang, Yung-Huang; Zhang, Wenjing; Zhu, Yihan; Han, Yu; Pu, Jiang; Chang, Jan-Kai; Hsu, Wei-Ting; Huang, Jing-Kai; Hsu, Chang-Lung; Chiu, Ming-Hui; Takenobu, Taishi; Li, Henan; et al. (ACS nano, 2014)
Monolayer molybdenum disulfide (MoS2) has become a promising building block in optoelectronics for its high photosensitivity. However, sulfur vacancies and other defects significantly affect the electrical and optoelectronic properties of monolayer MoS2 devices. Here, highly crystalline molybdenum diselenide (MoSe2) monolayers have been successfully synthesized by the chemical vapor deposition (CVD) method. Low-temperature photoluminescence comparison for MoS2 and MoSe2 monolayers reveals that the MoSe2 monolayer shows a much weaker bound exciton peak; hence, the phototransistor based on MoSe2 presents a much faster response time (<25 ms) than the corresponding 30 s for the CVD MoS2 monolayer at room temperature in ambient conditions. The images obtained from transmission electron microscopy indicate that the MoSe exhibits fewer defects than MoS2. This work provides the fundamental understanding for the differences in optoelectronic behaviors between MoSe2 and MoS2 and is useful for guiding future designs in 2D material-based optoelectronic devices.